ANALISIS IMPLEMENTASI APLIKASI SISTEM INFORMASI TERHADAP PENGELOLAAN KEUANGAN DALAM PELAKSANAAN BELANJA DAERAH PADA BKAD PROVINSI SULAWESI UTARA - Rumondor, Merlyn Delly; Tinangon, Jantje J.; Wokas, Heince R. N. (Universitas Sam Ratulangi, 2023)
Financial management through instruments in the form of applications, namely viralslot SIMDA which has been developed into FMIS and SIPD, is a necessity and a necessity in supporting performance in both the central and regional governments. This research is to analyze the implementation of information system applications on financial management in the implementation of regional expenditures at the BKAD of North Sulawesi Province. The methodology is descriptive qualitative viralslot. The results of the study are that first the implementation of regional spending through FMIS and after it are realized, recording transactions to SIPD. The policy for implementing regional spending as stated in SE.Governor of North Sulawesi Province. Second, there are communication and resource constraints in the form of applications. The three efforts to overcome communication obstacles are by communicating intensively with the Development Team at the Ministry of Home Affairs Data and Information Systems Center and the Central BPKP Development Team/Representative for North Sulawesi Province. Furthermore, efforts to overcome resource constraints in the form of applications are by adding bandwidth to the maximum limit at severalpoints and providing an FMIS application server at the BKAD of North Sulawesi Province viralslot.